2020
DOI: 10.1002/edn3.136
|View full text |Cite
|
Sign up to set email alerts
|

Application of eDNA metabarcoding in a fragmented lowland river: Spatial and methodological comparison of fish species composition

Abstract: Assessments of fish communities tend to rely on capture‐based methods that, due to sampling biases, can underestimate actual species richness. Alternatively, environmental DNA (eDNA) based metabarcoding is a noncapture approach that infers species richness and distribution by collecting and sequencing DNA present in the ecosystem. Here, eDNA metabarcoding was applied to the lower River Severn, a highly modified and impounded river, to identify the species present in the fish assemblage. Using a universal prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…By extrapolation of the detection data for freshwater fishes (Figure 4), we demonstrated the superior ability of eDNA metabarcoding for species richness estimation in this habitat. Our findings add to a growing body of literature supporting the use of eDNA for the analysis of freshwater fish communities in riverine systems (e.gAntognazza et al, 2021; Berger et al, 2020; Cilleros et al, 2019). However, we observed a distinct drop in species detection in the tidal stretches of the river Thames compared with that obtained by traditional survey methods, in which several lower tidal sites failed to produce any sequences.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…By extrapolation of the detection data for freshwater fishes (Figure 4), we demonstrated the superior ability of eDNA metabarcoding for species richness estimation in this habitat. Our findings add to a growing body of literature supporting the use of eDNA for the analysis of freshwater fish communities in riverine systems (e.gAntognazza et al, 2021; Berger et al, 2020; Cilleros et al, 2019). However, we observed a distinct drop in species detection in the tidal stretches of the river Thames compared with that obtained by traditional survey methods, in which several lower tidal sites failed to produce any sequences.…”
Section: Discussionsupporting
confidence: 72%
“…The eDNA metabarcoding signal we detected was representative of the pattern of fish communities known to exist within the catchment, from the upper freshwater reaches to the tidal Thames. Our study thus adds to a growing number of examples of eDNA metabarcoding being comparable, or even outperforming, traditional fish survey methods (i.e., electrofishing, visual surveys, acoustic telemetry, poisoning), across diverse aquatic environments including temperate rivers and canals (Pont et al, 2018; McDevitt et al, 2019; Antognazza et al, 2021), temperate and tropical lakes (Doble et al, 2020; Hänfling et al, 2016), and marine settings (Afzali et al, 2020). Although our results show the power and potential for the detection of fish diversity in freshwaters, they also illustrated the need for further refinement of eDNA collection in turbid estuaries.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…ASVs have been used for fish monitoring based on eDNA. Antognazza et al (2020) used ASVs to detect fish species composition in a fragmented lowland river and compared eDNA-based and long-term fishing monitoring results; the results showed that eDNA could detect species such as European shads (Alosa spp.) with high conservation value that were never sampled by capture techniques.…”
Section: Multispecies Detectionmentioning
confidence: 99%
“…Most comparisons of the wf-eDNA approach with traditional sampling methods to characterize ecological communities have been conducted at the local scale and show how wf-eDNA and traditional sampling methods represent community composition in lakes, reservoirs, and rivers (Murienne et al, 2019;Czeglédi et al, 2021;Gehri et al, 2021). Several studies have also shown that wf-eDNA is a complementary approach to traditional sampling methods to assess fish community composition in lakes and rivers (Shaw et al, 2016;Doi et al, 2019;Sard et al, 2019;Antognazza et al, 2021;Ritterbusch et al, 2022). In general, wf-eDNA may characterize a large number of taxa with less sampling effort than traditional sampling methods for detecting fish in low-diversity freshwater systems (McElroy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%